Tracing global progress: two decades of age-related macular degeneration research - Li-Yun Yuan; Liang-Pin Li; Xia Hua; Xiao-Yong Yuan (International Journal of Ophthalmology)
AIM: To conduct a comprehensive bibliometric analysis of age-related macular degeneration (AMD) research from 2002 to 2022, identifying key contributing countries, institutions, authors, journals, and research hotspots to inform future research directions. METHODS: Publications related to AMD were retrieved from the Web of Science Core Collection (WoSCC) database for the period January 1, 2002, to December 31, 2022. The search was limited to English-language articles and reviews. Bibliometric analysis was performed using Microsoft Excel 2021 for data management and annual publication analysis. Visualization and network analyses were conducted using VOSviewer, CiteSpace, and the Bibliometrix package in R. Collaboration networks among countries, institutions, authors, and journals were mapped. Keywords were analyzed for co-occurrence to identify research hotspots. Metrics such as H-index, total link strength (TLS), and citation counts were used to assess impact. RESULTS: A total of 16 715 publications were analyzed, showing a consistent increase in AMD research output over the past 20y, peaking at 1445 publications in 2021. The United States was the leading contributor with 31.8% of total publications, followed by China and the United Kingdom. The University of Melbourne emerged as the most productive institution with the highest TLS, indicating strong international collaborations. Professor Frank G. Holz was identified as the most influential author based on H-index and publication count. Investigative Ophthalmology & Visual Science was the most prolific journal and had the highest citation impact. Keyword co-occurrence analysis revealed four main research clusters: pathogenesis, therapy, epidemiology, and diagnosis. Emerging research hotspots included anti-vascular endothelial growth factor (VEGF) therapies, optical coherence tomography angiography, and artificial intelligence (AI) applications in diagnosis. CONCLUSION: The bibliometric analysis highlights significant growth and collaborative efforts in AMD research globally. Key contributors have advanced understanding in pathogenesis, therapeutic strategies, epidemiology, and diagnostic technologies. Future research should focus on interdisciplinary collaborations, novel therapeutic targets, personalized medicine, and technological innovations such as AI to effectively address the challenges posed by AMD.